Efek Ekstrak Sambiloto (Andrographis paniculata Nees) pada Ekspresi Telomerase dari Kanker Payudara Tikus yang Diinduksi dengan DMBA (Journal of Tropical Pharmacy and Chemistry, 2025)
It has been well documented that chemical carcinogen, 7.12 dimethylbenz(a)anthracene (DMBA),  plays a role in the incidence and growth of mammary cancer. Present study was designed to investigate the influence of Andrographis paniculata extract on telomerase activities on DMBA induced breast cancer in the female rat Sprague Dawley strain. DMBA-induced mammary cancer is a useful model to investigate the changes of epithelial cells that occur during mammary cancer progression. Mammary cancer model was induced 10 times twice a week by oral DMBA 20 mg/kg body weight. Mammary cancer occurred in 75 % animals nine weeks after oral administration of DMBA, it was represented with nodule on the mammary gland and the increasing of mammary gland volume compare with normal control F(1.8) = 731.711; p < 0.001. This study was also designed to investigate the effect of Andrographis paniculata extract mammary carcinoma induced by DMBA. Administration of three different dose of Andrographis paniculata (100 mg/kg, 300 mg/kg and 1000 mg/kg) had statistically different with mammary gland volume of DMBA treated rat F (4.17) = 92.777; p